Analisis Sistem Pengendalian Intern Kas Pada PT. Ira Widya Utama Medan - Putri Kemala Dewi Lubis; Adinda Ulina Barus (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to describe the application of the internal cash control system and analyze the internal control system for cash receipts and disbursements applied to PT. Ira Widya Utama in Medan, is it in accordance with the elements of the control system according to COSO. PT. Ira Widya Utama is a company engaged in construction services and housing development. The problems that arise in this study, where there is still evidence of receipt and proof of cash disbursements have not been serially numbered printed and are still contained in the supporting document records of the company's cash receipts transactions that have not been affixed with the